Intra-specific trophic variation in false killer whales (Pseudorca crassidens) from the southwestern South Atlantic Ocean through stable isotopes analysis - Riccialdelli, Luciana; Prosser Goodall, Rae Natalie (Mammalian Biology)
The false killer whale (Pseudorca crassidens) is a highly social top predator difficult to study in the wild because of its wide-ranging oceanic habits. Mass strandings offer good opportunities to gather ecological information about cetacean species. In this study we analyze a possible isotopic (δ13C and δ15N) variation in bone collagen among individual false killer whales that mass stranded on the south shore of the Strait of Magellan, Chile, in 1989, in relation to their ontogenetic classes, sex and total body length. We found an isotopic enrichment in δ13C and δ15N values from young and smaller to older and larger individuals, respectively. These isotopic shifts may reflect differences in foraging and diving capabilities, enabling older and larger individuals to feed more deeply in the water column and/or on larger prey. The lack of isotopic differences between females and males may suggests little evidence for sex-related resource partitioning in this group, as result of a possible coordination during feeding activities, e.g. food sharing as previous studies have found. We also found an important isotopic effect of lactation in both the carbon and nitrogen isotope composition of nursing calves, probably due to a prolonged nursing period (from 19 month to two years). This study integrate ecological information from several years to lifetime in relation to sex and total body length, obtaining information on possible changes linked to the development of foraging capabilities in false killer whale. Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Prosser Goodall, Rae Natalie. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina